Debonding of carbon fiber veil interleaved adhesively bonded GFRP joints via Joule heating - Caglar, Hasan (2022)
Carbon fiber veils are thin non-woven materials that enable debonding of adhesively bonded composites joints. The effects of three different carbon fiber veils on the mechanical, thermal and electrical characteristics of epoxy adhesive systems sandwiched in-between glass fiber reinforced polymer (GFRP) were examined. In comparison to the neat epoxy configurations, carbon fiber veil interleaving enhanced storage modulus, thermal diffusivity and lap shear strength (LSS) of the adhesive joints while lowering specific heat capacity (Cp) and glass transition temperature (Tg). Fourier-transform infrared spectroscopy (FTIR) analysis showed that the heated epoxy samples and composite samples made from interleaving carbon fiber veil sandwiched between two epoxy film adhesive layers at 100 °C for 1 min did not show any detectable change in their chemical structures. Surface roughness and water contact angle measurements were conducted to investigate the wettability of the GFRP adherends. Finite element coupled thermal-electric simulations and Machine Learning based solution displayed good agreement with Joule heating experiments. Thermomechanical debonding via Joule heating provided good debonding characteristics such as low force and time requirements, no fiber-tearing on the surface of the adherends and allowing selective heating of the bonded region of the joints.